Property of Melatonin of Acting as an Antihypertensive Agent to Antagonize Nocturnal High Blood Pressure: A Meta-Analysis (International Journal of Statistics in Medical Research, 2019)
Therapy of hypertension persisting in the course of nocturnal sleep has yielded rather disappointing results . Therefore, the research has focused on drugs such as melatonin acting in such a way so as to counteract the lack of fall in blood pressure during night time sleep. A meta-analysis has been planned by gathering only randomized controlled trials( RCTs), where melatonin was administered as a single dose at bedtime and compared with placebo.The efficacy was the "night time variation in systolic blood pressure" and the "night time variation in diastolic blood pressure". Safety endpoint was the possible occurrence of serious adverse events.Seven studies with 221 participants were pooled in the meta-analysis. Melatonin use was a predictor of significant decrease in nocturnal systolic blood pressure[SBP]( difference in means[MD]= -5.74 mm Hg; 95% CI: -6.07 to- 5.41 mm Hg; p